Addition of grape pomace flour in the diet on laying hens in heat stress: Impacts on health and performance as well as the fatty acid profile and total antioxidant capacity in the egg. (February 2019) - Reis, João H.; Gebert, Roger R.; Barreta, Mauricio; Boiago, Marcel M.; Souza, Carine F.; Baldissera, Matheus D.; Santos, Ingrid D.; Wagner, Roger; Laporta, Luciane V.; Stefani, Lenita M.; Da Silva, Aleksandro S.
Abstract: The aim of this study was to evaluate whether the addition of grape pomace flour (GPF) in the diet of laying hens at the end of the productive cycle and on heat stress could exert benefits on their health and performance, as well as egg quality. For this, 74-week-old laying hens (n = 64) were divided into four groups with four repetitions each, as follow: T0 (the control group; without GPF), T1 (1% GPF), T2 (2% GPF) and T3 (3% GPF) during 35 days. Percentage of laid eggs was higher in the group T1 compared to T0, and the feed intake was higher in the groups T1, T2 and T3 compared to T0. There was no difference regarding the chemical-physical composition of fresh eggs; however, eggs from GPF-fed chickens showed changes after storage regarding specific gravity, yolk index, pH of yolk, albumen and Haugh unit compared to T0. Fresh or stored egg yolk from GPF groups showed higher antioxidant capacity and lower lipid peroxidation compared to T0. GPF (3%) prevented the reduction of monounsaturated fatty acids in the yolk of stored eggs compared to T0. Glutathione peroxidase and superoxide dismutase activities, as well as total antioxidant capacity against peroxyl radicals were higher in the serum of laying hens that received GPF compared to T0, while lipid peroxidation was lower. In summary, the addition of GPF in the diet for laying hens at the end of the productive cycle can be beneficial for animal health and exerted positive effects in their performance and egg quality. Highlights: Heat stress in old laying hens negatively affects performace. The use of grape pomace flour (GPF) in the diet of laying hens promoted enhanced productive efficiency. The use of GPF in diet stimulated the antioxidant system, exerting beneficial properties on animal health. GPF in diet of hens was able to reduce egg lipid peroxidation and to increase antioxidant levels. GPF in diet contributed to improved internal egg quality, as well as to maintain yolk pH of stored eggs similarly to fresh eggs.